Use Of Quizwhizzer Media To Improve Vocabulary Skills In Mathematics Learning - Pramudyawardhani, Sri Rejeki; Arsito, Slamet; Amalia, Sofri Rizka (Integral (Jurnal Penelitian Pendidikan Matematika), 2024)
The aim of this research is to determine whether vocabulary abilities in mathematics learning after applying the QuizWhizzer media are better than vocabulary abilities in mathematics learning before applying the QuizWhizzer media. This research is experimental research. The population in this study were class XIII students at Al Mi'raj Talang Middle School. Meanwhile, the sample in this research was class VIII A. The data collection techniques in this research were tests and documentation. The test is used to determine vocabulary abilities in learning mathematics. Documentation is used to find out student data and photos of activities. Data analysis techniques are prerequisite tests: normality and homogeneity tests, data analysis tests: paired sample t test. Vocabulary abilities in mathematics learning after the application of the QuizWhizzer media are better than vocabulary abilities in mathematics learning before the application of the QuizWhizzer media .